A Note about the Finance Journal Rankings and Citation Counts - Luh-Yu (Louie) Ren (Asian Academy of Management Journal of Accounting and Finance, 2016)
The purpose of this study is to examine the (rank) correlation coefficient of five finance journal ranking methods from Harzing's Journal Quality List in 2016 and one citation count method from the Association Business Schools (ABS) Academic Journal Quality Guide in 2010. We also propose a new way of comparing the actual ranks from the above six journal ranking methods with the random ranks generated from Excel to address which finance ranking method deviates the most from a random ranking.